Risk Factor Analysis of the Incidence of Placenta Previa at RSUP Dr. Mohammad Hoesin Palembang in 2020–2021 - Dian Widia Lestari; Firmansyah Basir; Ziske Maritska; Hartati Hartati; Rara Inggarsih (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Placenta previa is a placenta that lies at the bottom of the uterus, above or very close to the internal cervical ostium. The exact cause of placenta previa is still unknown, but several factors have been associated with an increased risk of placenta previa. This study aims to determine the relationship between maternal age, parity, distance between pregnancies, history of placenta previa, history of cesarean delivery, history of curettage, assisted reproductive technology, multiple pregnancies, and fetal gender on the incidence of placenta previa at RSUP Dr. Mohammad Hoesin Palembang in 2020-2021. This study is an observational analytic study with a case control design. This study used secondary data from medical records of obstetric patients at RSUP Dr. Mohammad Hoesin Palembang in 2020-2021 that met the inclusion criteria and exclusion criteria. The study sample amounted to 100 people consisting of 50 cases and 50 controls. The results of bivariate analysis using the chi-square test and the fisher exact alternative test showed that maternal age (p=0.010), parity (p=0.038), history of cesarean delivery (p=0.000), and history of curettage (p=0.001) had a significant relationship with the incidence of placenta previa. Distance between pregnancies (p=0.204), history of placenta previa (p=0.242), and fetal sex (p=0.162) did not have a significant relationship with the incidence of placenta previa. The results of multivariate analysis using binary logistic regression test showed that the most influential risk factors for the incidence of placenta previa were history of cesarean delivery (OR=54.751) and history of curettage (OR=20.204). It can be concluded that a history of cesarean delivery and a history of curettage are the most influential risk factors for the incidence of placenta previa.